COD, TSS, nutrients and coliforms removals in UASB reactors in two stages treating swine wastewater - Ramires, Roseane Del'arco [UNESP]; Oliveira, Roberto Alves De [UNESP] (Associação Brasileira de Engenharia Agrícola, 2014)
The performance of two upflow anaerobic sludge blanket (UASB) reactors was evaluated in pilot scale (908 and 188 L), installed in series (R1 and R2), fed with swine wastewater with TSS around 5 and 13 g L-1. The UASB reactors were submitted to HDT of 36 and 18 h with VOL of 5.5 to 34.4 g COD (L d)-1 in the R1 and HDT of 7.5 e 3.7 h with VOL from 5.1 to 45.2 g COD (L d)-1 in the R2. The average removal efficiencies of COD ranged from 55 to 85% in the R1 and from 43 to 57% in the R2, resulting in values from 82 to 93% in the UASB reactors in two stage. Methane concentrations in the biogas were 69 to 74% with specific production from 0.05 to 0.27 L CH4 (g removedCOD)-1 in the R1 and of 0.10 to 0.12 L CH4 (g removedCOD)-1 in the R2. The average removal efficiencies were 61 to 75% for totalP, 39 to 69% for KN, 82 to 93% for orgN and 20 to 94% for Fe, Zn, Cu and Mn. The amN concentration were not reduced indicating the need to post-treatment for effluent disposal into water bodies. There were reductions of total coliforms from 99.8123 to 99.9989% and of thermotolerant coliforms from 99.9725 to 99.9999%. The conditions imposed to the UASB reactors in two stage provided high conversions of removedCOD into methane (up to 77%) and reductions of organic an inorganic pollution loads from swine wastewater.

Foi avaliado o desempenho de dois reatores anaeróbios de fluxo ascendente com manta de lodo (UASB) em escala-piloto (908 e 188 L), instalados em série (R1 e R2), para o tratamento de águas residuárias de suinocultura com concentrações médias de SST em torno de 5 e 13 g L-1. Os TDH foram de 36 e 18 h com COV de 5,5 a 34,4 g DQO (L d)-1 no R1 e TDH de 7,5 e 3,7 h com COV de 5,1 a 45,2 g DQO (L d)-1 no R2. As eficiências médias de remoção de DQO variaram de 55 a 85% no R1 e de 43 a 57% no R2, resultando valores de 82 a 93% nos reatores UASB em dois estágios. As concentrações de metano no biogás foram de 69 a 74%, com produções de 0,05 a 0,27 L CH4 (g DQOremovida)-1 no R1 e de 0,10 a 0,12 L CH4 (g DQOremovida)-1 no R2. Os valores médios de eficiência de remoção de Ptotal foram de 61 a 75%; de NK de 39 a 69%; de Norg. de 82 a 93%, e de Fe, Zn, Cu e Mn de 20 a 94%. As concentrações de N-am. não foram reduzidas, indicando a necessidade de pós-tratamento para disposição do efluente em corpos d'água. Houve redução de coliformes totais de 99,8123 a 99,9989%, e de coliformes termotolerantes de 99,9725 a 99,9999%. As condições impostas aos reatores UASB em dois estágios propiciaram reduções acentuadas da carga poluidora orgânica e inorgânica das águas residuárias de suinocultura, com conversão de até 77% da DQO removida em metano.
Remoções de DQO, sólidos, nutrientes e coliformes em reatores UASB em dois estágios tratando água residuárias de suinocultura
Keywords: Volumetric organic load; Methane; N and P removal; Metal removal; Suspended solids; Carga orgânica volumétrica; Metano; Remoção de N e P; Remoção de metais; Sólidos suspensos